Does Trade Lead to a Race to the Bottom in Environmental Standards? Another Look at the Issues - Erlinda M. Medalla; Dorothea C. Lazaro (Philippine Institute for Development Studies (PIDS), 2005)
With rising globalization and advances in technology, the interrelationship between trade and the environment has increasingly become a pressing issue across the globe. This paper seeks to contribute to the discussion, mainly by looking at some theoretical underpinnings, learning from some findings in the literature and offering additional empirical evidence in relation to what is happening in the globalized world. For example, is there evidence that international trade encourages a "race to the bottom" in environmental regulations? Are developing countries more likely to export polluting products? On the other hand, are calls for environmental protection no more than disguised protectionism? What is the state of the global/multilateral regime dealing with trade and environment? Accordingly, the paper looks at some theoretical underpinnings and findings on trade and environment linkage. This is followed by a discussion on the current trade structure of products by pollution-intensity classification between developed and developing countries. The paper also contains two sections dealing respectively with some observations on environmental regulations and the treatment of environment in the multilateral agenda. Finally, the paper concludes by highlighting the need to pursue trade and environment policies in tandem.
Keywords: 330; trade and environment linkages; race-to-the-bottom; pollution haven; Kyoto Protocol; Handelsliberalisierung; Umweltpolitik; Internationale Umweltpolitik; Umweltstandard